2011
DOI: 10.1186/1477-3155-9-14
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of nanoparticle internalization in mammalian cells by high resolution X-ray microscopy

Abstract: BackgroundQuantitative analysis of nanoparticle uptake at the cellular level is critical to nanomedicine procedures. In particular, it is required for a realistic evaluation of their effects. Unfortunately, quantitative measurements of nanoparticle uptake still pose a formidable technical challenge. We present here a method to tackle this problem and analyze the number of metal nanoparticles present in different types of cells. The method relies on high-lateral-resolution (better than 30 nm) transmission x-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 44 publications
1
61
0
Order By: Relevance
“…The one-pot, reducing agent free synthesis produced clean and monodisperse AuNPs with high colloidal stability. Optical microscopy and TEM tests on cell specimens in vitro confirmed that the AuNPs were internalized by endocytosis303132 and did not penetrate into the cell nuclei. The nanoparticles were biocompatible with the cell lines we tested up to a concentration of 2.0 mM in the culture media.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The one-pot, reducing agent free synthesis produced clean and monodisperse AuNPs with high colloidal stability. Optical microscopy and TEM tests on cell specimens in vitro confirmed that the AuNPs were internalized by endocytosis303132 and did not penetrate into the cell nuclei. The nanoparticles were biocompatible with the cell lines we tested up to a concentration of 2.0 mM in the culture media.…”
Section: Resultsmentioning
confidence: 90%
“…Our own research indicated that different cancer cell lines can internalize large amounts AuNPs without affecting viability303132.…”
mentioning
confidence: 97%
“…A 5 MeV proton energy was chosen as lower proton energies are common in the Bragg peak which is colocated with the tumor in proton therapy and 5 MeV was the lowest energy for which a large self‐absorption loss was not observed. The nanoparticle sizes simulated cover the range of typical single nanoparticle sizes as well as the size of nanoparticle aggregations observed in in vitro experiments …”
Section: Methodsmentioning
confidence: 99%
“…Achievable XCT image resolution ranges from the millimeter to nanometer scale depending on equipment, experimental parameters, and the size and volume of the imaged specimen (Chen et al 2011;Graafsma and Martin 2008;Ketcham and Carlson 2001;Kinney and Nichols 1992). Although a well-established technique, micro-XCT has only recently been applied to study the structure and behavior of wood and wood-based composites (Hass et al 2010(Hass et al , 2012Kamke et al 2014;Mannes et al 2009aMannes et al , b, 2010Mayo et al 2010;Modzel 2009;Modzel et al 2011;Muszyński 2009;Paris et al 2014;Standfest et al 2012;Steppe et al 2004;Trtik et al 2007), this is the theme of the present work.…”
Section: Introductionmentioning
confidence: 98%